Graphics 2 : Angebote Druckgraphik und Multiples der internationalen aktuellen Kunst 1960 - 1981. - Schellmann & Klüser, München (München : Verlag Schellmann & Klüser, 1981)
Albers, Joseph ; Alfano, Carlo ; Arakawa ; Arman ; d'Arcangelo, Allan ; Baselitz, Georg ; Beuys, Joseph ; Bohrmann, Karl ; Broodthaers, Marcel ; Buren, Daniel ; Chia, Sandro ; Chillida, Eduardo ; Christo ; Close, Chuck ; Cucchi, Enzo ; Dibbets, Jan ; Dine, Jim ; Flavin, Dan ; Erben, Ulrich ; Gitlin, Michael ; Graubner, Gotthard ; Hamilton, Richard ; Heerich, Erwin ; Heizer, Michael ; Hockney, David ; Dekkers, Ger ; Hutchinson, Peter ; Indiana, Robert ; Johns, Jasper ; Jones, Allen ; Jorn, Asger ; Judd, Don ; Kelly, Ellsworth ; Kienholz, Edward ; Kitaj, Ron ; Klapheck, Konrad ; Kounellis, Jannis ; Lausen, Uwe ; LeWitt, Sol ; Lichtenstein, Roy ; Lüpertz, Markus ; Mangold, Robert ; Marden, Brice ; Merz, Mario ; Merz, Gerhard ; Morris, Robert ; Nestler, Wolfgang ; Nauman, Bruce ; Newman, Barnett ; Nevelson, Louise ; Nitsch, Hermann ; Oldenburg, Claes ; Oppenheim, Dennis ; Paladino, Mimmo ; Paik, Nam June ; Palermo ; Paolozzi, Eduardo ; Panamarenko ; Penck, A.R. ; Rainer, Arnulf ; Rauschenberg, Robert ; Ray, Man ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Rot, Diter ; Ryman, Robert ; Serra, Richard ; Shapiro, Joel ; Stella, Frank ; Tapies, Antoni ; Twombly, Cy ; Warhol, Andy ; Wesselmann, Tom
Duits
boek